Delphi Study on the Difficulties of Safety Practice Implementation in Indonesia: A Case of Transportation Infrastructure Projects (International Journal of Built Environment and Sustainability, 2025)
Despite the fact that health and safety practice at work has been promoted over decades, occupational injuries and fatalities continue to plague the construction industry particularly in developing economies like Indonesia. What are the major difficulties in implementing safety practices in Indonesian, and how do these challenges differ from those identified in previous research? This study aims at investigating the difficulties of implementing safety practices in Indonesian, specifically in the case of transportation infrastructure projects (TIPs). A perusal of past research successfully identified 16 fundamental difficulties to implement safety practices, mostly in the field of construction industry. Based on the expert’s opinions, two difficulties were added by considering the characteristic of TIPs and domestic issue. A two-round Delphi survey was employed to obtain 16 experts’ consensus on major fundamental difficulties in implementing safety practice at TIPs. The experts were academia, government agencies and practitioners having national occupational safety certificate and TIPs experienced. Most of experts agreed that difficulty in changing the workers’ mindset and unsafe outward demeanour, the uniqueness of TIPs (complexity, massive heavy equipment and adverse site condition), adversity of conducting safety supervision on TIP’s sites, lack of safety awareness of workers (ignorance and disobey) and difficulty to enforce national standard and regulation as the five topmost difficulties of safety practice implementation at TIPs. The findings on the key issues hampering the implementation of safety practices in TIPs are very important for the project’s stakeholders in designing strategy or program to improved safety implementation in similar projects. This study contributes to the existing literature by providing a detailed analysis of safety challenges specific to Indonesian transportation infrastructure projects, which have unique characteristics such as large-scale operations and complex infrastructure. While the Delphi survey method is effective for obtaining expert consensus, it may be subject to biases.
Keywords: Safety practice, Difficulties, Infrastructure development, Indonesia, Delphi survey .